ENGLISH AND THE TIBETAN TONGUE - Nikalje, Varada M. (THE PRIMARY TEACHER, 2011)
The linguistic landscape of India is remarkable in the richness of its variety. A minuscule part of the linguistic mosaic of India is formed by the Tibetans, who arrived in India as refugees and settled in various parts of India. The Tibetan children studying in primary classes have the Tibetan medium of instruction. English is taught as a second language in these classes. This paper attempts to address English language teaching within this unusual combination of diversity in India’s linguistic landscape.